The impact of digitalization on educational achievement: a literature review from a sociological perspective - Hatos, Adrian (Calitatea Vieții, 2019)
There is still a great optimism concerning the impact of ICT (Information and Communications Technology), including CAI (Computer Assisted Instruction) on the effectiveness of education. The article is a brief synthesis, mostly with a sociological leaning, of the current empirical literature devoted to the various ways in which digitalization has an influence upon the results of education. We found that the investigations of educational impact of digitalization follows the trend from the general literature concerning the social effects of ICT which reveals an empirical perspective of multi-layered divisions in which the first and the second levels (or orders) are the most thoroughly researched and theorized while current developments tentatively regard issues of third, fourth and international digital divisions. As a general overview of the domain it can be concluded that as it develops the more and more the initial optimism vanes making space for anguish over the possible socially divisive potential of ICT use in education. The digital revolution in education not only does not solves previous issues but apparently creates new ones as differences in access, in skills and in use patterns are able to increase the various offline gaps between people of different socio-economic backgrounds.